Agricultural greenhouse CO2 utilization in anaerobic-digestion-based biomethane production plants: A techno-economic and environmental assessment and comparison with CO2 geological storage. (15th May 2019) - Oreggioni, G.D.; Luberti, M.; Tassou, S.A.
Highlights: Design of CO2 -enriched greenhouses using captured CO2 from a biogas to biomethane upgrading unit. Economic and environmental assessment of the proposed CO2 Utilization route. Comparison with CO2 geologically stored plant configurations. CO2 utilization route exhibits better economic performance than the CO2 storage case. Net greenhouse gas emission savings for the Utilization case are strongly dependent on system/boundary assumptions. Abstract: Anaerobic digestion plants enable the production of power, heat and fuel. Biogas can be upgraded to biomethane fulfilling grid injection requirements by separating CH4 from CO2 . By- product CO2 could be geologically stored or utilized as a feedstock to produce valuable goods, enabling in both cases negative climate change impact fuel production. CO2 utilization could as well improve plant economics, as a consequence of the profits related to the commercialization of the final products whilst allowing further emission reductions. In this paper, a techno-economic assessment of the use of the CO2 by-product in CO2 -enriched agricultural greenhouses for tomato production is discussed. The results of the research show that, depending on the operating mode and the design approach, the use of a greenhouse enables the recovery of 14–67% of the by-product CO2 when the internal CO2 concentration is kept at 1000 ppm. In addition, it is estimated that the associated heat and power demand ranges from 0.097 to 0.138 kWhth /kg of used CO2 and 0.04–0.05 kWe /kg of used CO2, respectively. Revenues related to the tomato production are partially offset by the greenhouse capital investment and operating costs; however, a net profit between 16 and 19 p/kg of used CO2 was calculated, leading to a net profit of 1.3–1.6 p/kWh of injected biomethane. These results show that CO2 utilization is technically feasible and economically more convenient than CO2 storage. While both geological storage and CO2 utilization would allow negative climate change impact fuel production, the net greenhouse emission savings for the utilization configuration were found to be strongly dependent on the assumptions regarding fuel substitution for the produced biomethane.